Optimal impulsive blood glucose control through multiple injections. (November 2021) - Mirzaee, Alireza; Dehghani, Maryam; Mohammadi, Mohsen
Highlights: An insulin pattern to control the blood glucose level in diabetic patients is designed. While most researches assume continuous insulin pattern which is applicable only by insulin pump, this paper assumes multiple daily injections. The problem of determining optimal time and dosage of insulin injection is formulated as an optimal control problem. Different patient conditions such as different exercise level, food intake, … are considered. The algorithm is tested in various scenarios and the optimal time and dosage of insulin is determined. Abstract: Despite numerous advances in glycemic control based on the artificial pancreas, Multiple Daily Injections (MDI) are still the most common method in type 1 diabetes mellitus patients. In the present study, an optimal impulsive control approach is introduced to attain a safe range of blood glucose considering the daily life factors, including food intake and exercise. Depending on the food intake and exercise, the proposed impulsive control signal can determine the optimal exogenous insulin dosages per day. MDI program for type 1 diabetic patients due to several overeating conditions, with and without exercise, is a blood glucose control program. This program can conveniently help the patients to manage unwanted conditions such as missed insulin injections or meals. The recommended approach is investigated on the comprehensive glucose-insulin model of diabetic subjects, and it effectively determines the time and magnitude of the insulin injection dosages. Based on the simulation results, three times injection mode in terms of hypoglycemia and severe hyperglycemia risks is efficient and dosages times and magnitudes are well determined in different food intake scenarios by the proposed approach. This approach can significantly help physicians to regulate blood glucose in a sophisticated optimal, reliable route.